Sistem Prediksi Penjualan di Toko Dasni Menggunakan Metode Double Exponential Smoothing - Tasya Kurnia Sabila; Lelah Lelah; Didik Indrayana (STEKOM PRESS, 2022)
In developing a business or sale is to follow technological developments including the use of systems for buying and selling interactions. There are already many sellers who make buying and selling interactions online. In addition, to develop a business, it is also necessary to predict future sales so that the seller knows and prepares the number of goods to be sold to avoid shortages or excess quantities of goods. To find sales predictions, various methods can be used, one of which is Double Exponential Smoothing method. Double Exponential Smoothing method is the time series method that uses data from the past to predict the next period. The data processed is sales data at Dasni clothing stores for one year. The results obtained are in the form of a sales prediction system for the next 3 months period which calculates the level of prediction accuracy using MAPE (Mean Absolute Percentage Error) with the smallest error sought because the smaller the error, the more accurate it is to predict the number of sales in the next period. This prediction system is also designed using the PHP programming language.